Optimizing Social Media as a Marketing Media for Kampoeng Farmers' Coffee Products (Case Study of PT. Galang Smart Indonesia) - Syam, Agus; Yuniarti, Sri; Isma, Andika (PT. EQUATOR SINAR AKADEMIA, 2024)
This research aims to determine the optimization of social media in marketing Kampoeng Farmer Coffee Products at PT. Galang Smart Indonesia. The research method used is descriptive qualitative research using data collection methods through observation, interviews and documentation. The data that has been collected is processed using data reduction steps, data presentation, and drawing conclusions/verification. The research results show that the management of Instagram and WhatsApp social media in marketing Kampoeng farmer coffee products can be said to be quite optimal. Optimization is carried out starting from the use of features on Instagram social media such as Feed, Instastory, Direct Message, Caption, Tags and Hashtags, and Reels. On WhatsApp Business, the catalog feature, status and message features are used automatically. By optimizing social media, Instagram and WhatsApp, it influences the level of sales at PT. Galang Smart Indonesia